EVALUACIÓN DE LA SUPLEMENTACIÓN ALIMENTICIA EN LA CEBA DE TORETES MESTIZOS CHAROLAIS AL SOGUEO, EN EL SUR DE LA AMAZONIA ECUATORIANA - Saca Minga, Edison Rodrigo (2021)
The present work was carried out with the purpose of evaluating the effect of food supplementation on the fattening of young bulls in a rope grazing system. The trial lasted 90 days, 12 mestizo Charolais bulls from 12 to 18 months of age and an average weight of 397.4 kg were used; distributed in two experimental groups of six animals each, using a randomized block design. The treatments were: T1 supplement with 15% of crude protein (corn, palm kernel, soybeans, molasses and mineral salts) and T2 control only grazing. The following variables were studied: bromatological composition of the pasture and the supplement, feed consumption, weight gain, feed conversion, profitability and cost-benefit ratio; Analysis of variance and Tukey's test were performed on each of the variables. The results show appreciable crude protein (CP) content of the white and purple gramalot grasses (Axonopus scoparius) with an average of 11.88%; although the crude fiber content (FC) was high; the supplementary ration presented 79.35% DM, 14.85% PC and 15.75% F.C. Treatment one (with supplement) registered a higher consumption of dry matter (p ≤ 0.001) with 13.4 kg day-1; greater weight gain (946 g) and better feed conversion (14.4 kg), (p ≤ 0.001); while the economic indicators were acceptable in the two experimental groups. It is concluded that food supplementation improves technical and economic indicators in beef cattle, maintained in a rope grazing system. Keywords: fattening, grazing, supplement, behavior, productive, profitability